2009 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops 2009
DOI: 10.1109/cvpr.2009.5204202
|View full text |Cite
|
Sign up to set email alerts
|

Using closed captions to train activity recognizers that improve video retrieval

Abstract: Recognizing activities in real-world videos is a diffi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…For increasingly large and complex datasets, manual labeling will become prohibitive. Automatic labeling using video subtitles [48] and movie scripts [20,26,73] is possible in some domains, but still requires manual verification. When using an incremental approach to image harvesting such as in [55], the initial set will largely affect the final variety of action performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For increasingly large and complex datasets, manual labeling will become prohibitive. Automatic labeling using video subtitles [48] and movie scripts [20,26,73] is possible in some domains, but still requires manual verification. When using an incremental approach to image harvesting such as in [55], the initial set will largely affect the final variety of action performances.…”
Section: Discussionmentioning
confidence: 99%
“…Several automatic approaches have been proposed, for example using web image search results [55], video subtitles [48] and subtitle to movie script matching [20,26,73]. Gaidon et al [40] present an approach to rerank automatically extracted and aligned movie samples but manual verification is usually necessary.…”
Section: Obtaining and Labeling Training Datamentioning
confidence: 99%
“…They again used commentary as a "view" for action recognition with success. To train an activity classifier in an automated fashion, without the requirement of any manual labeling, Sonal and Mooney [7] make use of broadcast closed captions and used the system for video retrieval. There are a few works which focus on captioning in sports settings.…”
Section: Related Workmentioning
confidence: 99%
“…22 However, the authors' approach only used a small dataset of seven videos and did not consider high-level natural language concept features in predicting sentiment or for aspect extraction. Besides this, caption mining was previously used in the context of scene segmentation, 23 video activity recognition, 24 and movie genre classification. 25 Targeting the automotive domain 26 demonstrated that emotional and factual knowledge, such as a sentiment of a product feature, can be extracted from text using a combination of lexical methods including SenticNet.…”
Section: Related Workmentioning
confidence: 99%